Report on purchasing patterns of the government of St. Vincent and the Grenadines - English, Jacqueline (CEDP St. MichaelBB, 1993)
Seeks to identify marketing opportunities within the government sector in St. Vincent and the Grenadines for goods produced within CARICOM.